Sosialisasi Penerapan Prinsip Good Manufacturing Practice (GMP) dalam Meningkatkan Daya Saing Produk Olahan Ikan yang Unggul di Kelurahan Mallawa, Kabupaten Barru, Sulawesi Selatan - Nurlela - Machmuddin (Universitas Muhammadiyah Sidenreng Rappang, 2025)
The community service activity in Mallawa Village, Barru Regency, aims to educate the public about the importance of applying the principles of Good Manufacturing Practice (GMP). The activity implementation method is carried out thru the stages of preparation, activity implementation consisting of education/socialization and training or direct practice in making fish floss, packaging, and evaluating the results of the activity by distributing feedback questionnaires. The activities carried out to achieve the objectives are: 1) education on good food processing methods (handling); 2) accounting, namely determining the cost of processed fish products; 3) marketing regarding marketing strategies for processed fish products; 4) minimizing waste, which involves processing fish waste into liquid organic fertilizer. The product resulting from hands-on practice is fish floss. The evaluation results of the feedback questionnaire showed that out of 35 participants, 80 percent were satisfied with the education and training provided. The results of the mentoring provided showed that some participant members had attempted to produce fish floss and package several types of anchovies. Packaging is not only done for processed fish products but also for other products that are characteristic of the partner location, such as turmeric powder, banana chips, and mango sour. The conclusion of this activity is that educational, practical, and participatory methods are used to achieve the goals, including processing fish into value-added products, with GMP principles applied throughout the activity. Of course, nature optimizes direct practices by the community, and the role, support, and guidance of the government and relevant agencies are still highly anticipated.